2017
DOI: 10.1002/ecm.1264
|View full text |Cite
|
Sign up to set email alerts
|

Coupling biogeochemical tracers with fish growth reveals physiological and environmental controls on otolith chemistry

Abstract: Biogeochemical tracers found in the hard parts of organisms are frequently used to answer key ecological questions by linking the organism with the environment. However, the biogeochemical relationship between the environment and the biogenic structure becomes less predictable in higher organisms as physiological processes become more complex. Here, we use the simultaneous combination of biogeochemical tracers and fish growth analyzed with a novel modeling framework to describe physiological and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 99 publications
3
46
0
Order By: Relevance
“…Intra-regional differences in growth arose from variation in environmental influences and population dynamics. Few studies have applied fine-scale growth profiles (Grammer et al 2017), despite their value. Here, we developed seasonally resolved chronologies, which provided nuanced predictions of growth trends which encapsulated and accounted for fluctuations throughout a whole year that may have been otherwise overlooked in broader annual chronologies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-regional differences in growth arose from variation in environmental influences and population dynamics. Few studies have applied fine-scale growth profiles (Grammer et al 2017), despite their value. Here, we developed seasonally resolved chronologies, which provided nuanced predictions of growth trends which encapsulated and accounted for fluctuations throughout a whole year that may have been otherwise overlooked in broader annual chronologies.…”
Section: Resultsmentioning
confidence: 99%
“…Limited work has investigated the application of these sclerochronological approaches on temporal scales smaller than annual measurements. Consequently, there is potential to investigate the value of finer scale (such as seasonally or monthly resolved) growth histories, which may offer a higher-resolution approach and capture small-scale, inter-annual variation relating to environmental fluctuations (Izzo et al 2016, Grammer et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that Jervis Bay, the most marine-dominated estuary, had the lowest average Sr:Ca ratio in the juvenile otoliths. While there was no significant effect of fish length found in the univariate Sr PERM-AN OVA (Table S3), the fish from Jervis Bay were, on average, the smallest (Table S1) and there were therefore possibly some size-related intrinsic effects on otolith chemistry here such as ontogenetic changes in diet (Buckel et al 2004, Engstedt et al 2012 or differing physiology in small P.saltatrix (Grammer et al 2017). Indeed, decreases in Ba:Ca and Sr:Ca ratios have previously been demonstrated in P. saltatrix when switching diet from prawns to fish (Buckel et al 2004).…”
Section: Juvenile Otolith Chemistry Differencesmentioning
confidence: 96%
“…growth and diet) and extrinsic (e.g. temperature, salinity) factors in addition to a simple relationship with water chemistry (Sturrock et al 2014, Grammer et al 2017. A recent meta-analysis highlighted this by demonstrating that whilst salinity was the primary driver of both Ba and Sr, Sr was also influenced by factors including the ecological niche, condition, diet and ontogeny of individual species (Izzo et al 2018).…”
Section: Elemental Profilesmentioning
confidence: 99%
“…Despite positive indications, our ability to interpret variations in vertebrae chemistry as tracers of elasmobranch environmental histories is still limited, and further evaluations of the effects of extrinsic factors, including temperature, salinity, water chemistry and pH, are paramount to better understand common trends across species and environments, as well as to gain insights into the scale and magnitude at which we are able to reconstruct elasmobranchs' past environmental histories or patterns of habitat use. Moreover, the extent to which intrinsic factors can buffer or magnify environmentally mediated element incorporation in calcified structures and how that potentially introduces interpretation error in environmental and life history reconstructions remain uncertain (Kalish 1989;Sturrock et al 2014Sturrock et al , 2015Loewen et al 2016;Grammer et al 2017;Reis-Santos et al 2018). Here, we found that shark condition (Fulton's K) increased Mn : Ca and Li : Ca (for the laboratory sharks only) and assume that this is evidence of an intrinsic control or physiological influence on element uptake and vertebrae chemical composition (as per Izzo et al 2015), even if further investigation is required.…”
Section: Elementmentioning
confidence: 99%